2023
DOI: 10.1088/1361-6560/acc309
|View full text |Cite
|
Sign up to set email alerts
|

Accurate segmentation of head and neck radiotherapy CT scans with 3D CNNs: consistency is key

Abstract: Objective: Automatic segmentation of organs-at-risk in radiotherapy planning CT scans using convolutional neural networks (CNNs) is an active research area. Very large datasets are usually required to train such CNN models. In radiotherapy, large, high-quality datasets are scarce and combining data from several sources can reduce the consistency of training segmentations. It is therefore important to understand the impact of training data quality on the performance of auto-segmentation models for radiotherapy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…A tangible manifestation of the "garbage in, garbage out" principle within HNC contouring is exemplified in a study by Henderson et al 9 Their findings revealed that models trained on a small set of consistent contours (ie, strictly following guidelines) aligned more closely with the reference standard test data than those trained on a vast array of inconsistent contours ( Fig. 1 ).…”
Section: Insight 1: DL Auto-contouring Algorithms Require High-qualit...mentioning
confidence: 87%
“…A tangible manifestation of the "garbage in, garbage out" principle within HNC contouring is exemplified in a study by Henderson et al 9 Their findings revealed that models trained on a small set of consistent contours (ie, strictly following guidelines) aligned more closely with the reference standard test data than those trained on a vast array of inconsistent contours ( Fig. 1 ).…”
Section: Insight 1: DL Auto-contouring Algorithms Require High-qualit...mentioning
confidence: 87%
“…The planning CT datasets available for the present analysis had a slice thickness of 3 mm, which is in the range radiotherapy head and neck image analysis methods are currently developed and evaluated on [30,42]. A lower slice thickness will increase the resolution in the z-dimension but also the computational time for the mapping analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Given that FDG PET has exhibited significantly higher specificity and numerically superior sensitivity compared to contrast-enhanced CT imaging in identifying metastatic lymph nodes in the head and neck [ 41 ], the application of the proposed image analysis techniques to extensive cohorts with FDG PET imaging holds particular promise. The planning CT datasets available for the present analysis had a slice thickness of 3 mm, which is in the range radiotherapy head and neck image analysis methods are currently developed and evaluated on [ 30 , 42 ]. A lower slice thickness will increase the resolution in the z-dimension but also the computational time for the mapping analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These algorithms, primarily based on CNNs, have shown remarkable accuracy and efficiency in delineating OARs and tumor targets and have rapidly entered routine clinical practice 87 . A noteworthy development is the integration of 3D CNNs, which better capture the spatial relationships in volumetric data, leading to improved contour accuracy compared to traditional approaches 88 . Generative adversarial networks (GANs) have been employed to augment training datasets and to perform data normalization, enhancing model robustness across different imaging modalities and protocols 89 .…”
Section: Ai Integration Into Routine Practicementioning
confidence: 99%
“… 87 A noteworthy development is the integration of 3D CNNs, which better capture the spatial relationships in volumetric data, leading to improved contour accuracy compared to traditional approaches. 88 Generative adversarial networks (GANs) have been employed to augment training datasets and to perform data normalization, enhancing model robustness across different imaging modalities and protocols. 89 AI applications in radiation treatment planning have also advanced notably.…”
Section: Ai Integration Into Routine Practicementioning
confidence: 99%